1997
DOI: 10.1021/es970185i
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in Drinking Water Distribution Systems:  A Major Contributor of Copper and Lead to Wastewaters and Effluents

Abstract: Corrosion, even in water supply systems with treatment to reduce it, can be a major contributor of copper and lead to both treated municipal (publicly owned treatment works, POTW) wastewater effluents and biosolids. Lead and copper concentrations were measured at several points in the water/wastewater systems of four Massachusetts municipalities. Domestic wastewater was found to contain concentrations of lead and copper significantly higher (p < 0.05) than those in source waters. For each facility, the median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 6 publications
0
25
0
2
Order By: Relevance
“…In the past decade, our knowledge of the detrimental effects of trace and ultratrace quantities of metals in our environment has greatly increased [2][3][4]. These metals may cause cancers and other serious diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, our knowledge of the detrimental effects of trace and ultratrace quantities of metals in our environment has greatly increased [2][3][4]. These metals may cause cancers and other serious diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…One study found that 60–75% of all lead was leached in the first 125 mL and 95% in the first 250 mL of flow from brass fixtures (Gardels & Sorg, 1989). Two more recent field studies seem to support this observation as well (Knobeloch et al, 1998; Isaac et al, 1997). The first study reported that the dominant source of lead and copper in domestic wastewater is the corrosion of domestic plumbing, which included all houses in the service area irrespective of their age (Isaac et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
“…For the Langmuir model, the following equation was used: q eq = q m C eq (K d +C eq ) [3] where q eq and C eq correspond to the milligrams of Cd adsorbed per one gram of the polymer and the residual Cd concentration in the solution when in equilibrium and K d and q m are Langmuir constant and maximum capacity of adsorption for this model. Freundlich isotherm constants were calculated with the equation: lnq eq = n lnC eq + lnK F [4] where K F and n are the Freundlich constants characteristic of the polymer system.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…The solid phase extraction (SPE) technique has been widely used in the preconcentration of trace and ultra trace amounts of analytes to enhance the sensitivity of determination (2). A large range of special chelating resins of SPE reagents, which are highly selective for particular ions, have been prepared in the past decade (3). Chelating resins are generally efficient in the adsorption of trace metal ions because of their physical and chemical stability.…”
Section: Introductionmentioning
confidence: 99%